2013
DOI: 10.1080/13607863.2013.814105
|View full text |Cite
|
Sign up to set email alerts
|

Medical conditions in geriatric hoarding disorder patients

Abstract: Hoarding disorder (HD) in late life is associated with increased risk for fire, falling, poor sanitary conditions, disability, and health risks. However, research on the health status of individuals with HD is limited. Hoarding symptoms and the resulting clutter may exacerbate health conditions and lead to improper management of medical illnesses.Objective-The purpose of this study is to characterize the health status of older adults with hoarding. The rates of medical conditions will be compared to a non-psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Psychiatric comorbidity in HD is very high, with a majority of individuals meeting criteria for comorbid depressive and anxiety disorders . Furthermore, substantial evidence suggests the presence of diminished cognitive functions, such as attention, memory, or executive functions; impaired behavioral self‐control; and significant medical illness . The SDS, which is a broader measure of impairment, does not specify a cause of impairment, and it may be that these other factors contribute to residual functional impairment even after successful treatment of HD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric comorbidity in HD is very high, with a majority of individuals meeting criteria for comorbid depressive and anxiety disorders . Furthermore, substantial evidence suggests the presence of diminished cognitive functions, such as attention, memory, or executive functions; impaired behavioral self‐control; and significant medical illness . The SDS, which is a broader measure of impairment, does not specify a cause of impairment, and it may be that these other factors contribute to residual functional impairment even after successful treatment of HD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Second, hoarding symptoms may be mitigated in older adults by identifying and treating at-risk individuals, perhaps identified on the basis of family history, given the heritable nature of HD (5, 6, 18, 59), Thus, in older individuals, one should particularly focus on identifying problems with discarding items, and combine the treatment as usual with interventions that may be specific to the aging brain. For example, Ayers et al (2014) (60) found that incorporating cognitive rehabilitation techniques focused on improving executive function significantly improved hoarding outcomes in older adults (58). Such approaches, when implemented earlier in life, may help to decrease disorganization, restore deficits in inhibition, and improve outcomes later in life.…”
Section: Discussionmentioning
confidence: 99%
“…HD is associated with poor overall physical and mental health, and those with the disorder are more likely to have comorbid chronic medical conditions (e.g., fibromyalgia, chronic fatigue syndrome, obesity) and mental health disorders (Tolin, Frost, Steketee, Gray, & Fitch, 2008). In one study of older adults, 90% of participants with HD reported having a medical condition compared with 44% of members of a nonpsychiatric peer comparison group (Ayers, Iqbal, & Strickland, 2014). Diabetes, sleep apnea, arthritic complications, hematological conditions, and various cardiovascular problems were also found more frequently in those with HD, and it was hypothesized that these medical issues may be due to self‐neglect and a lower frequency of visits to a primary care physician (Ayers et al, 2014 Counselors need to help clients establish healthy routines in addition to addressing underlying mental health concerns.…”
Section: Diagnosismentioning
confidence: 99%